EMPLOYING THE FORMATIVE RELATIONS BETWEEN DECORATION AND MUSIC IN THE ABBASID ERA - Assit.prof. Athmar Hameed Karim; Assit. prof Salah Hadi Bashan (Scholar Express Journal, 2022)
This research is concerned with studying (the employment of formative relationships between the art of decoration and music in the Abbasid era), and it contains four chapters. The research problem dealt with the mechanisms of employing the formative relations of the art of decoration and music, and accordingly the problem of the current research was determined in the following questions: Is there a relationship between decorative art and music implemented in the Abbasid era? What are the mechanisms and frameworks used by the components of the art of decoration and music in the Abbasid era? The aim of the research is to identify the formative relationships by revealing the linking relationships between decoration and music within the following frameworks: 1. The basic meaning of decoration and music. 2. The contextual meaning of decoration and music. 3. The expressive meaning of decoration and music. 4. The contextual social value of decoration and music. The research was determined in revealing the formative relations between the decorative arts and music in the Abbasid era (750 -1258) AD (132 - 656 AH) the decorative formations from the Mustansiriya school carried out with plaster and yellow bricks) and musical pieces (Ishaq Al-Mawsili, Abu Al-Hasan Ali bin Nafeh Zaryab, Aliyah bint Al-Mahdi Al-Absa) and concluded the first chapter by defining the terms mentioned in the research. As for the second chapter, it included the theoretical framework that came with three sections, the first was concerned with the study of decoration in the Islamic era, the second topic was focused on a detailed study of music in the Abbasid era, and the third topic focused on revealing the bonds of the link between the art of decoration and music under the title of overlapping genres of arts. As for the third chapter, it was devoted to research procedures and defining its community and sample according to objective foundations, and the researchers adopted it to build an analysis form and then select and analyze samples within the (descriptive-analytical approach). Of the validity and stability of the tool. As for the fourth chapter, it included the results, conclusions, recommendations, and suggestions, and one of the most important findings of the research is the existence of a strong correlation between the decorative arts and musical pieces, followed by a list of sources and references, and then the appendices and a summary of the research in English.
Keywords: Decoration; Music; Abbasid Era